(untitled) (Austrian Journal of Statistics, 2014)
We consider random graphs with node degrees drawn independently from a power- law distribution. By computer simulation we study two aspects of graph robustness: preserving graph connectivity and node saving in the forest fire model, considering two types of graph destruction: the removal of nodes with the highest degrees and equiprobable node extraction.